Holstein Friesian genetic introgression and its association with estimated breeding values and expected producing ability in Karan Fries cattle - DAS, MANAS KUMAR; SINGH, AVTAR; DIXIT, SAT PAL; JAYAKUMAR, S; UPADHYAY, ARPAN (The Indian Journal of Animal Sciences, 2015)
Introgression levels inform us about the admixture of genes within the genome of 2 populations due to crossing among them. The present investigation was carried out to determine the introgression levels of Holstein Friesian (HF) into crossbred Karan Fries (KF) cattle, developed under controlled breeding programme at National Dairy Research Institute (NDRI), Karnal, India. The association of HF introgression levels with estimated breeding values (EBVs) and expected producing ability (EPA) of KF cattle were also estimated. Eighteen reported microsatellite markers were used in the study and the HF introgression levels were assessed through STRUCTURE 2.3.4 program. Inheritance percentages of HF in the studied KF cattle showed varying degree of levels ranged between 50 and 75%. The results showed that the average HF introgression per cent in KF cattle was 52.30% ranging from 15.96 to 87.21%. The EBV and EPA showed significant association with increasing HF introgression levels. However, HF inheritance levels had nonsignificant effect on those traits. Introgression levels may be the future tool for explaining the productive performances of crossbreds than inheritance levels.